APA Handbook of Industrial and Organizational Psychology, Vol 3: Maintaining, Expanding, and Contracting the Organization. 2011
DOI: 10.1037/12171-003
|View full text |Cite
|
Sign up to set email alerts
|

Motivating employees.

Abstract: What motivates individuals at work? How do we know when behavior is the result of motivation or some other internal or external factor? What can managers do to maintain or increase the motivation of their employees? These questions and others like them have been a central focus of industrial and organizational (I/O) psychology for many years (G. E. Latham, 2007;Steers, Mowday, & Shapiro, 2004;Viteles, 1953). The high level of interest in work motivation by practitioners and researchers may be attributed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 447 publications
(937 reference statements)
2
82
0
Order By: Relevance
“…Obstfeld, 2005), but we know of no motivation research that suggests that motivation may also be a function of innovation. This idea could open up new research opportunities in motivation, because it suggests that classic equations of motivation, like those in expectancy (Vroom, 1964) or equity (Adams, 1963) theories, may be variable within activities as well as between them, and can be studied as such, helping to address the recent interest that motivation scholars have shown in trying to explain how people's motivation can change over time as they participate in the same activity (Diefendorff & Chandler, 2011).…”
Section: Contributions Of An Integrated Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Obstfeld, 2005), but we know of no motivation research that suggests that motivation may also be a function of innovation. This idea could open up new research opportunities in motivation, because it suggests that classic equations of motivation, like those in expectancy (Vroom, 1964) or equity (Adams, 1963) theories, may be variable within activities as well as between them, and can be studied as such, helping to address the recent interest that motivation scholars have shown in trying to explain how people's motivation can change over time as they participate in the same activity (Diefendorff & Chandler, 2011).…”
Section: Contributions Of An Integrated Modelmentioning
confidence: 98%
“…We do so because (1) physical energy is one of the many resources invested when effort is exerted (Diefendorff & Chandler, 2011), (2) it can be difficult to distinguish, when engaged in the practical considerations of empirical research, from time, attention, or other resources-in-use (e.g. Vancouver et al, 2008), and (3) the limiting factor for whether or not energy is invested in activities is not the availability of glucose/ATP, but whether or not a person feels energetic activation for those activities (Marks, 1977;Moller et al, 2006;Thayer, 1989).…”
Section: Energy As Resources: a Building Block In An Integrative Modementioning
confidence: 99%
“…It has been linked to increased employee productivity and organizational revenue, as well as employees' well-being and thriving (Steers, Mowday, & Shapiro, 2004). Given its important role, a good deal of research has focused on the type and extent of motivation employees experience (e.g., Diefendorff & Chandler, 2011;Latham & Pinder, 2005). Within this research area, a prominent focus has been on how the satisfaction of needs, or "some type of internal tension or arousal" (Kanfer, 1990: 81), enhances employee motivation.…”
mentioning
confidence: 99%
“…Work values represent a particular set of values that guide and motivate specific behaviors performed in the workplace (Diefendorff & Chandler, 2011;Latham, 2012). Empirical evidences have demonstrated that SWVs exert direct influences on job performance.…”
Section: Effects Of Work Values On Job Performancementioning
confidence: 99%